Effectiveness of Postoperative Pain Management and Postoperative Emergency Pain Management at Prof.Dr. I.G.N.G. Ngoerah General Hospital - I Putu Pramana Suarjaya (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif (PERDATIN) / The Indonesian Society of Anesthesiology and Intensive Care (INSAIC), 2023)
Background: Early postoperative recovery has undergone many developments. Early mobilization, early nutritional intake, and adequate postoperative pain management are the scope of early postoperative recovery. The principle of postoperative pain management starts from preoperative evaluation which includes medical and psychological conditions, medication history, history of chronic pain, drug abuse, and previous postoperative treatment regiments to guide postoperative pain management plans. Method: This research is an analytical observational study, carried out at Sanglah Hospital Denpasar from June 2021 to December 2021. The accessible population of this study was all postoperative patients at the Central Surgical Installation and the Emergency Room at Sanglah Hospital Denpasar who were consulted by the Acute Pain Service (APS) team. Inclusion criteria were all patients who underwent surgical procedures under general and regional anesthesia, ASA physical status 1-3, and age above 18 years. Results: There were 166 patients managed by continuous intravenous postoperative analgesia (73.1%), 43 patients by epidural postoperative analgesia (18.9%), and 18 patient-controlled analgesia/PCA (7.9%). The most widely used intravenous regiment was fentanyl by 85 (37.4%).Conclusion: This study shows incidences number of acute postoperative pain in the elective and emergency department at Sanglah Hospital Denpasar gave good results with a much lower incidence of pain compared to the existing literature.